Morpho-physiological and anatomical responses of two Urochloa hybrids under shade: Dataset article - Hernandez Alvarez, Urys Mileth; Mayorga, Mildred; Cardoso Arango, Juan Andrés (Elsevier, 2024)
Silvopastoral systems are an important strategy for sustainable livestock production. However, to expand their implementation, it is crucial to identify and develop forage materials that maintain good production and quality while being tolerant to shade conditions as well as other biotic and abiotic stresses. A field trial was conducted to evaluate the morpho-anatomical and agronomic responses of two Urochloa hybrids (Camello and Talisman) under two light conditions: shade (28 % light intensity) and full exposure. The trial followed a randomised complete block design with split-plot arrangement, where each treatment corresponded to a plot with three replications. Morphological and anatomical parameters were recorded in three technical replicates of each replication. Histological leaf sections were analysed for the percentage of adaxial epidermis, abaxial epidermis, vascular tissue, colourless parenchyma, Kranz sheath, bulliform cells, sclerenchyma, and chlorenchyma. Measurements in leaf included relative chlorophyll concentration, leaf area, leaf length, and leaf width. Evaluations in plant included height and number of tillers. Agronomic parameters such as plant cover and dry biomass were recorded for each plot. Additionally, six leaf imprints were made on the leaf undersides to observe stomatal morphology, and their length was recorded. Furthermore, plants from each treatment were grown in soil-filled tubes within the same plots. Root system photographs were taken, and in three replications per treatment, root length, root diameter, root volume, root surface area, and the depth at which 95 % of roots were concentrated (D95) were determined. These data can be utilised by the scientific community and breeders to conduct analyses and meta-analyses to identify shade tolerance mechanisms and develop genetic materials tolerant to changing climatic conditions while being optimal for use in silvopastoral systems.